Strategi Manajemen Konflik sebagai Upaya Peningkatan Produktivitas Organisasi - Ni Kadek Mawar Salistha; Ni Made Cantika Kumala Dewi; Komang Tania Andini; Nella Melenia (Pusat Riset dan Inovasi Nasional, 2026)
Conflict is an inevitable phenomenon in organizational life due to differences in backgrounds, interests, values, and ways of thinking among individuals within an organization. Conflict is often perceived as a barrier to productivity; however, when managed effectively, it can become a catalyst for improved performance and organizational innovation. This study aims to examine conflict management strategies as an effort to enhance organizational productivity. The research employs a library research method by reviewing relevant management textbooks, scholarly journals, and academic articles related to organizational conflict, conflict management, and productivity. The findings indicate that the application of appropriate conflict management strategies, such as collaboration, compromise, and accommodation, can improve communication quality, reduce workplace tension, and increase employee motivation and job satisfaction. Furthermore, conflict can serve as an opportunity for growth if leaders adopt a proactive approach and create a framework for resolving disputes constructively. Effective conflict management not only resolves immediate issues but also fosters a positive organizational culture where employees feel valued and understood. Therefore, effective conflict management plays a strategic role in creating a conducive work environment and enhancing sustainable organizational productivity. By leveraging conflict as a tool for collaboration, organizations can create innovative solutions and achieve long-term success.